Transformasi Sikap Profesional dan Karakter Tangguh Siswa: Studi Empiris di SMA Happy Family School Surabaya - Subadi, Lucky Cahyana; Tjahjono, Laura Mahendratta; Budidharmanto, Lexi Pranata; Wahyudi, Julietta Cesilia; Purwadi, Kezia Victory (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to enhance students’ professional attitude and resilience by focusing on key competencies such as communication, leadership, problem-solving, time management, collaboration, and professional ethics. These skills equip students to adapt and compete in dynamic environments.Method – This study adopts an adapted classroom action research approach with a limited trial, focusing on quantitative assessment. Unlike traditional CAR, this study emphasizes a single intervention phase, using pre-tests and post-tests to evaluate students’ professional attitudes and resilience through an eight-item test. Data analysis was conducted using SPSS for comparative hypothesis testing. Findings – The results indicate no significant difference between students' pre-test (3.52) and post-test (3.45) scores, and as shown by the paired sample t-test p-value (0.654 > 0.05), the intervention did not lead to a statistically significant improvement. Several factors contributed to the lack of progress in students’ understanding of professionalism and resilience, including inadequate structured guidance (scaffolding), the absence of reflective sessions after industry visits, and limited discussions on pre-test results. Research Implications – This study highlights that the success of experience project learning in enhancing students' professional attitudes and resilience depends on structured scaffolding. Teachers and mentors must provide systematic guidance throughout the learning process. This study’s limitation is its small sample size at Happy Family High School, which may affect generalizability to other institutions with different student demographics and learning environments.